Tests of different monetary aggregates for the monetary models of the exchange rate in five ASEAN countries. - Lee, Chin; Habibullah, Muzafar Shah; Mohamed, Azali (Taylor & Francis (Routledge), 2009)
This study examines the usefulness of divisia money, relative to simple sum money, for exchange rate modelling in a period of rapid financial deregulation. This comparison is conducted using the monetary model of the exchange rate. In the long-run modelling, the divisia money is significantly superior to simple sum money in the case of Malaysia and the Philippines while indifferent for Indonesia, Singapore and Thailand.